The cannabinoid agonist WIN55,212-2 increases intracellular calcium via CB1 receptor coupling to Gq/11 G proteins - Lauckner, Jane E; Hille, Bertil; Mackie, Ken (Proceedings of the National Academy of Sciences - PNAS, 2005)
Central nervous system responses to cannabis are primarily mediated by CB(1) receptors, which couple preferentially to G(i/o) G proteins. Here, we used calcium photometry to monitor the effect of CB(1) activation on intracellular calcium concentration. Perfusion with 5 microM CB(1) aminoalkylindole agonist, WIN55,212-2 (WIN), increased intracellular calcium by several hundred nanomolar in human embryonic kidney 293 cells stably expressing CB(1) and in cultured hippocampal neurons. The increase was blocked by coincubation with the CB(1) antagonist, SR141716A, and was absent in nontransfected human embryonic kidney 293 cells. The calcium rise was WIN-specific, being essentially absent in cells treated with other classes of cannabinoid agonists, including Delta(9)-tetrahydrocannabinol, HU-210, CP55,940, 2-arachidonoylglycerol, methanandamide, and cannabidiol. The increase in calcium elicited by WIN was independent of G(i/o), because it was present in pertussis toxin-treated cells. Indeed, pertussis toxin pretreatment enhanced the potency and efficacy of WIN to increase intracellular calcium. The calcium increases appeared to be mediated by G(q) G proteins and phospholipase C, because they were markedly attenuated in cells expressing dominant-negative G(q) or treated with the phospholipase C inhibitors U73122 and ET-18-OCH(3) and were accompanied by an increase in inositol phosphates. The calcium increase was blocked by the sarco/endoplasmic reticulum Ca(2+) pump inhibitor thapsigargin, the inositol trisphosphate receptor inhibitor xestospongin D, and the ryanodine receptor inhibitors dantrolene and 1,1'-diheptyl-4,4'-bipyridinium dibromide, but not by removal of extracellular calcium, showing that WIN releases calcium from intracellular stores. In summary, these results suggest that WIN stabilizes CB(1) receptors in a conformation that enables G(q) signaling, thus shifting the G protein specificity of the receptor.